Pathophysiology of Skin Aging: Role of Oxidative Stress, Inflammation, and Dermal Remodeling - Baiq Merna Merta Sari; Imey Pinasty Harianto Putri; Atriska Citra Muliana; Shira Shalsabina Shafitri; Janiya Abdila Ilmiah; Ihza Namira Athalia; Rashieka Salma Aulia; Gantha Narendra Josafat; Muhammad Hilmy As Shiddiq; I Nyoman Yudayana Indratama; Rangga Cahya Prasetya; Nurhidayati Nurhidayati (Indonesian Journal of Health and Medical Education, 2026)
The skin, as the largest organ of the human body, plays a vital role in protecting the internal systems from external environments. As age increases, the skin undergoes two types of aging: intrinsic, caused by genetic and hormonal factors, and extrinsic, due to environmental factors such as ultraviolet (UV) radiation and pollution. The aging process is characterized by a decrease in fibroblasts, which are responsible for producing collagen and elastin, leading to a reduction in skin strength and elasticity. Oxidative stress resulting from the accumulation of reactive oxygen species (ROS) contributes to DNA damage and triggers inflammatory responses that accelerate aging, manifesting as wrinkles and sagging skin. Chronic inflammation, induced by ROS, further supports premature aging by increasing inflammatory substances that cause redness and irritation of the skin. Additionally, dermal remodeling is a physiological process essential for maintaining healthy skin. Still, it can become pathological if there is an imbalance between synthesis and degradation of the extracellular matrix, thereby hastening signs of aging such as wrinkles and sagging skin. In efforts to combat skin aging, several pharmacological aspects, such as topical therapies using sunscreens, retinoids, and alpha hydroxy acids (AHAs), have proven effective. Furthermore, systemic antioxidant supplementation also contributes to skin condition improvement. This comprehensive review provides valuable insights into the mechanisms of skin aging, the importance of skincare, and therapeutic strategies to counteract premature aging.